Clinical Ethics and Nutrition Support - Schwartz, Denise Baird (Journal of Nutritional Therapeutics, 2012)
Nutrition support should be considered optional when this therapy is not in congruence with an individual’s wishes based on quality of life goals, during the end-of-life period. Ethical dilemmas, dealing with nutrition therapy, are often due to lack of early communication between individuals, their family, and healthcare providers. Landmark young adult ethical court cases, dealing with nutrition therapy, reveal that this is not just a topic for the elderly. Healthcare literacy, multicultural populations, and different faiths add to the diversity of perspectives on healthcare decisions dealing with withholding or withdrawing nutrition therapy. These dilemmas are preventable if action steps are taken to improve the current healthcare clinical ethics model. Healthcare decision-making in advance should be considered by the individual and their family as an opportunity to communicate and plan for the future rather than a taboo topic. Healthcare facilities need to develop a proactive, integrated, structured process for healthcare ethical decision-making with measurable outcomes and shared best practice. Resources and toolkits are available to educate both the healthcare professional and the public on advance care planning